(untitled) (Indonesian Sports Justice Review, 2024)
While sports are an essential tool for social mobility and community empowerment, rural youth in Indonesia face significant challenges in accessing sports programs and facilities. This paper examines the barriers that rural communities encounter in sports development, including geographical isolation, lack of resources, and limited government investment. Through field research in several rural areas of Indonesia, the study identifies the gap between urban and rural sports infrastructure, as well as the disparities in athletic opportunities. It explores the roles of government, NGOs, and local sports clubs in addressing these challenges and proposes a model for developing sustainable sports programs that provide equal opportunities for rural youth. The paper highlights successful case studies of community-driven initiatives and recommends strategies to overcome systemic inequalities, such as mobile sports units, government grants, and public-private partnerships.